A rare earth modified KNN-LT lead-free piezoelectric ceramic and preparation method thereof
By introducing trace amounts of Sm2O3 into KNN-LT lead-free piezoelectric ceramics and adopting specific processes, the problem of strong temperature dependence of ceramic electrical properties is solved, the temperature stability and electrical properties are improved, and the application field is broadened.
Patent Information
- Application Number
- CN202310284371.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-22
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-03-22
AI Technical Summary
The electrical properties of existing KNN lead-free piezoelectric ceramics are highly dependent on temperature, have low density, have too high dependence on temperature, and have poor repeatability.
Rare earth modified KNN-LT lead-free piezoelectric ceramics are prepared by introducing trace amounts of Sm2O3 into KNN-LT lead-free piezoelectric ceramics and using specific ball milling and sintering processes, with the chemical formula of 0.95 (K0.55, Na0.45) NbO3-0.05LiTaO3-xmol.%Sm2O3.
The temperature stability and electrical properties of the ceramic are improved. The piezoelectric constant d33 is between 154 and 237pC/N, the electromechanical coupling coefficient Kp is between 30.15 and 43.7%, the mechanical quality factor Qm is between 101 and 107, and the Curie temperature is Tc is between 373 and 392℃, broadening its application field at high temperatures.
Smart Images

Figure CN116639974B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of piezoelectric electronic ceramic materials, and in particular to a rare earth modified KNN-LT lead-free piezoelectric ceramic and a preparation method thereof. Technical Background
[0002] Traditional piezoelectric ceramic lead zirconate titanate (PZT) has been widely used in transducers, filters, sensors and other fields. However, due to the toxicity of lead, the latest environmental protection standards have put forward the demand for lead-free piezoelectric ceramics.
[0003] KNN-based lead-free piezoelectric ceramics have attracted extensive attention and research from researchers due to their high Curie temperature and ultra-high piezoelectric coefficient. However, KNN ceramics prepared by traditional processes still have problems such as low density, high dependence of the piezoelectric coefficient on temperature, and poor repeatability.
[0004] Patent 2013104826961 introduces a KNN-LT lead-free piezoelectric ceramic and its preparation method. In this patent, the composition of the KNN-LT lead-free piezoelectric ceramic is (1-x)(K 0.5 ,Na 0.5 )NbO 3 -xLiTaO 3 This technology realizes the product's d 33 The maximum value can be 167pC / N, and the maximum value of the electromechanical coupling coefficient Kp is 37.3%. At the same time, after the introduction of LT in this technology, the Qm value of the product drops rapidly. Moreover, the patent does not involve the piezoelectric coefficient under high temperature conditions.
[0005] In the patent CN 113563073 A, a highly stable lead-free piezoelectric ceramic and its preparation method, people have developed a KNN-MT-BZT lead-free piezoelectric ceramic, whose composition is: (1-xy)(0.50KNbO 3 -0.50NaNbO 3 )-xMgTiO 3 -yBa(Zr 0.5 Ti 0.5 ) 3 +zSm 2 O 3 ; Among them, x = 0.03 ~ 0.07, y = 0.04 ~ 0.08, z = 0.008 ~ 0.02. However, the technical components are too complicated, and it needs to add a large amount of Sm to improve the electromechanical coupling coefficient of piezoelectric ceramics. Summary of the invention
[0006] In view of the problem that the electrical properties of existing KNN lead-free piezoelectric ceramics are highly dependent on temperature, the present invention provides a lead-free piezoelectric ceramic material containing a trace amount of Sm, having good electrical properties and good temperature stability, and a preparation method thereof.
[0007] The present invention discloses a rare earth modified KNN-LT lead-free piezoelectric ceramic, wherein the rare earth modified KNN-LT lead-free piezoelectric ceramic is made of Sm 2 O 3 The KNN-LT lead-free piezoelectric ceramic is modified, wherein the rare earth modified KNN-LT lead-free piezoelectric ceramic contains 0.01% to 0.7% Sm per mole of the KNN-LT lead-free piezoelectric ceramic. 2 O 3 .
[0008] Preferably, the present invention provides a rare earth modified KNN-LT lead-free piezoelectric ceramic, wherein the rare earth modified KNN-LT lead-free piezoelectric ceramic is represented by the following chemical formula:
[0009] 0.95(K 0.55 ,Na 0.45 )NbO 3 -0.05LiTaO 3 -xmol.%Sm 2 O 3 ;
[0010] Furthermore, x mol.%, indicates that x mol.% of Sm is introduced into 1 mol of KNN lead-free piezoelectric ceramic. 2 O 3 .
[0011] Furthermore, x is 0.2 to 0.6, and more preferably 0.2 to 0.4. The incorporation of an appropriate amount of samarium oxide in the present invention can refine the ceramic grains and obtain a dense and uniform ceramic microstructure. On the other hand, the refinement of the grains will lead to the refinement of the electric domains inside the ceramic, which is beneficial to enhance the coordination of the electric domain deflection. In addition, the appearance of the electric domain polarity microregion will increase the relaxation coefficient of the ceramic, enhance the dielectric stability of the KNN-LT ceramic at high temperature, and broaden the high temperature application field of lead-free KNN-LT piezoelectric ceramics.
[0012] The present invention provides a method for preparing a rare earth modified KNN-LT lead-free piezoelectric ceramic, comprising the following steps:
[0013] S1: Potassium source, sodium source, niobium source, lithium source, tantalum source and samarium source (Sm source) are prepared according to the chemical formula of rare earth modified KNN-LT lead-free piezoelectric ceramics, and the other components of the prepared raw materials except the Sm source are put into a ball mill, and organic matter is used as a solvent, and a high-energy ball mill is used for mixing and ball milling for at least 15 hours, preferably 20 to 25 hours, at a speed of 250 to 300 r / min, preferably 270 to 290 r / min, and the fully mixed powder is sieved and put into a corundum crucible and covered, and pre-calcined at 840 to 860° C. for 100 to 140 minutes, preferably 115 to 125 minutes, to obtain a pre-calcined powder; the potassium source, sodium source, niobium source, lithium source, tantalum source and samarium source are at least one of oxides, carbonates and bicarbonates;
[0014] S2: Grind and crush the pre-burned powder and put it into the ball mill again with the prepared samarium source (Sm source) and carry out secondary ball milling at a speed of 240-280r / min, preferably 260r / min for at least 15h. After ball milling, add 3-8wt.%, preferably 5wt.% of PVA organic adhesive to granulate to obtain a ceramic powder with good fluidity, regular shape and large average particle size (i.e., spare ceramic powder); press the spare ceramic powder into shape to obtain a ceramic green body.
[0015] S3: The ceramic green body is placed in a muffle furnace for sintering. The sintering process is divided into two stages. The first stage is 0-550°C, and the heating rate is less than or equal to 4°C / min, preferably 1.5-2.5°C / min, so that the organic matter such as PVA introduced in the granulation process can be fully escaped; the second stage is heated to 1100-1150°C at a heating rate of 4.5-10°C / min, preferably 4.5-6°C / min, and kept warm for at least 100min, preferably 115-135min.
[0016] S4: polishing the upper and lower surfaces of the sintered ceramic sample, coating the sample with silver electrodes, drying the sample, and then heat treating the sample at 550 to 650° C., preferably 590 to 610° C., for 10 to 20 minutes to obtain a silver-coated ceramic sample;
[0017] S5: The silvered ceramic sample is polarized in silicone oil under the conditions of 60-100°C silicone oil bath and maintained at a high voltage DC electric field of 1-4 kV / mm, preferably 1.8-2 kV / mm for 10-30 min, preferably 25 min.
[0018] The chemical formula of the rare earth modified KNN-LT lead-free piezoelectric ceramic is: 0.95 (K 0.55 ,Na 0.45 )NbO 3 -0.05LiTaO 3 -xmol.%Sm 2 O3 .
[0019] Preferably, in the preparation method of a rare earth modified KNN-LT lead-free piezoelectric ceramic of the present invention, in S1, the molar ratio is first converted into a mass ratio, and then the required mass of each component under a given total mass is weighed. The raw materials potassium carbonate, sodium carbonate, lithium carbonate, niobium oxide, and tantalum oxide are placed in a zirconium oxide ball mill, and anhydrous ethanol is used as a solvent. After mixing and ball milling for 20 hours at a high-energy ball mill with a rotation speed of 270 to 290 r / min, the fully mixed powder is sieved and placed in a corundum crucible and covered. It is pre-calcined at 840 to 860°C for 115 to 125 minutes to obtain a pre-calcined powder.
[0020] Furthermore, in the ball milling process described in S1, the mass ratio of various media in the ball mill is raw material: grinding ball: alcohol is equal to 1:1:1.2.
[0021] Furthermore, the particle size of the grinding balls is selected to be 0.1 to 1.0 cm, wherein the particle size of the small grinding balls is 0.5±0.05 cm, the particle size of the medium grinding balls is 0.8±0.05 cm, and the particle size of the large grinding balls is 1.1±0.05 cm. Furthermore, the mass ratio of the large, medium, and small grinding balls is 1:1.5:1.
[0022] In S2, the doping element Sm is added to the ball mill in the form of oxide particles. 2 O 3 Add to the ball mill in the form of particles. 2 O 3 The particle size of the particles is 70 to 90 microns, preferably 75 to 80 microns.
[0023] In S2, the second ball milling is performed for 18 to 25 hours.
[0024] Furthermore, during the granulation process of S2, a water bath heating at 75-85°C is used, and continuous stirring is required to prevent the PVA and the powder from being unevenly mixed and settling.
[0025] Furthermore, the ceramic powder obtained in S2 with good fluidity, regular shape and large average particle size (i.e., the spare ceramic powder) has an average particle size of 200 to 250 microns.
[0026] Furthermore, during the green compacting process of S2, care should be taken to avoid the powder from piling up on one side when filling, otherwise the powder will move relative to the pressure and cause delamination or cracking.
[0027] In S2, ceramic powder is added The mold was slowly loaded with a pressure of 100 MPa and maintained at this pressure for 20 seconds to obtain a ceramic green body.
[0028] Furthermore, in the sintering process of S3, the powder obtained after the secondary ball milling is buried in the corundum crucible for sintering. In order to further improve the effect, a double-layer crucible can be used to protect the sintered and pressed ceramic sheet.
[0029] Furthermore, during the sintering process of S3, the heating rate of the first stage was 2°C / min, and the temperature was kept for 2 hours to ensure that the adhesive slowly and fully overflowed and reduce the generation of pores inside the ceramic. The heating rate of the second stage was 5°C / min, and the temperature was kept for 2 hours to ensure that the ceramic grains grew fully, and finally the furnace was air-cooled.
[0030] In S4, after polishing the upper and lower surfaces of the sintered ceramic sample, a silver electrode is coated by a soft brush, dried in an oven at 80°C for 1 hour, and then heat treated at 600°C for 10 to 20 minutes.
[0031] Furthermore, during the silvering process of S5, a silver electrode is completely coated on one side of the sample and a silver electrode with a diameter of 6 mm is coated on the other side, which can ensure a precise effective area.
[0032] Compared with the prior art, the benefits of the present invention are:
[0033] The present invention provides a rare earth element doped KNN-LT lead-free piezoelectric ceramic formula with high temperature stability. The present invention firstly uses 5wt.% LiTaO 3 The KNN ceramics were modified by doping, and the orthorhombic-tetragonal phase interface was constructed inside, which greatly improved the piezoelectric properties of the KNN ceramics. Then, a trace amount of rare earth element samarium oxide was introduced to dope the KNN-LT ceramics, that is, 0.95 (K 0.55 ,Na 0.45 )NbO 3 -0.05LiTaO 3 -xmol.%Sm 2 O 3 , improve the squareness of the ceramic interior and further expand the stability of KNN ceramics.
[0034] The KNN-LT lead-free piezoelectric ceramic formula provided by the present invention has excellent piezoelectric properties in all aspects. Its piezoelectric constant d 33 =154~237pC / N, electromechanical coupling coefficient Kp=30.15~43.7%, mechanical quality factor Qm=101~107, Curie temperature Tc=373~392℃.
[0035] Furthermore, when x=0.4, that is, the piezoelectric ceramic formula is 0.95 (K 0.55 ,Na 0.45 )NbO 3 -0.05LiTaO3 -0.4mol.%Sm 2 O 3 At this time, the ceramic not only has a polycrystalline phase boundary structure where tetragonal phase and orthorhombic phase coexist, but also has a relatively excellent piezoelectric coefficient. At the same time, the temperature range of the two phases coexisting in the ceramic formula is relatively wide, and the piezoelectric coefficient can remain stable from room temperature to about 125°C, which has strong practical application value. At this time, the relaxation coefficient of the product is as high as 1.675.
[0036] Furthermore, when x=0.6, that is, the piezoelectric ceramic formula is 0.95 (K 0.55 ,Na 0.45 )NbO 3 -0.05LiTaO 3 -0.6mol.%Sm 2 O 3 At this time, the internal structure of the ceramic is a single tetragonal phase structure, and the phase structure will not change with temperature within the Curie temperature. The piezoelectric coefficient of this formula ceramic can remain stable from room temperature to about 350°C, greatly broadening the application scenarios of this formula lead-free piezoelectric ceramic.
[0037] Furthermore, the present invention adopts KNN raw material powder burying and sintering in a corundum crucible and double-layer crucible protection sintering and pressing of the ceramic sheet, the ceramic has high density and excellent piezoelectric and ferroelectric properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The XRD scanning data diagram and partial magnified diagram of the embodiments and comparative examples of the present invention are shown.
[0039] Figure 2 The SEM scans and partial magnified images of the embodiments and comparisons in the present invention.
[0040] Figure 3 The piezoelectric coefficient, electromechanical coupling coefficient and temperature aging resistance performance of the embodiments and comparative examples of the present invention are shown in FIG.
[0041] Figure 1 Where x=0 is the XRD pattern of the product obtained in Comparative Example 4, x=0.2 is the XRD pattern of the product obtained in Comparative Example 1, x=0.4 is the XRD pattern of the product obtained in Example 1, x=0.6 is the XRD pattern of the product obtained in Example 2, x=0.8 is the XRD pattern of the product obtained in Comparative Example 2, and x=1.0 is the XRD pattern of the product obtained in Comparative Example 3. Figure 1 It can be seen that Sm 3+The ions have entered the KNN-LT lattice and have no adverse effects on the main phase structure. According to the degree of peak separation of the (001) / (100) and (002) / (200) diffraction peaks near 32° and 46°, Example 1 is a polymorphic phase boundary structure in which tetragonal and orthorhombic phases coexist, Example 2 is a single tetragonal phase structure, and Comparative Example 3 is a pseudocubic phase structure.
[0042] like Figure 2 As shown, with the addition of Sm, the grains of KNN-LT ceramics are significantly refined, and the temperature at which the ceramics reach final densification gradually increases. The grains in the ceramics of Example 1 are small and uniform, and have the highest density.
[0043] like Figure 3 As shown, Example 1 has the most dense and uniform microstructure, and at the same time, it has a polycrystalline phase boundary structure with two phases coexisting inside, so it has the highest piezoelectric coefficient and electromechanical coupling coefficient. However, the polycrystalline phase boundary is directly related to temperature, so at about 125°C, the piezoelectric performance degrades. In addition, the addition of Sm can improve the tetragonality of the internal structure of the ceramic. The internal structure of the ceramic in Example 2 is a single tetragonal phase, far away from the polycrystalline phase boundary, and the piezoelectric coefficient is slightly worse than that of Example 1, but its piezoelectric coefficient can still remain stable at about 350°C, which greatly improves the application value of this type of lead-free piezoelectric ceramics in actual production. DETAILED DESCRIPTION
[0044] In the embodiment of the present invention, the temperature change rate is d 33 The change at different temperatures; the calculation method is:
[0045] TvD 33 =|Δd 33 / d 33 (25℃)|
[0046] where Δd 33 Calculated by the following formula:
[0047] Δd 33 =d 33max -d 33min
[0048] Among them, Tvd 33 is the temperature change rate; d 33 (25℃) means the product temperature at 25℃ 33 .
[0049] Example 1
[0050] A lead-free KNN-LT piezoelectric ceramic formula, the chemical formula of which is: 0.95 (K 0.55 ,Na 0.45 )NbO 3 -0.05LiTaO3 -0.4mol.%Sm 2 O 3 .
[0051] The preparation method of the above-mentioned ceramic is as follows:
[0052] Ingredients: First convert the molar ratio into mass ratio according to the chemical structural formula, and then weigh out the required mass of each component such as sodium carbonate, potassium carbonate, lithium carbonate, niobium oxide, tantalum oxide, and samarium oxide.
[0053] Mixing: Put the raw materials potassium carbonate, sodium carbonate, lithium carbonate, niobium oxide and tantalum oxide into the zirconium oxide ball mill, use anhydrous ethanol as solvent, ZrO 2 Grinding balls (grinding ball particle size is selected to be 0.1-1.0 cm, among which the small grinding ball particle size is 0.5±0.05 cm, the medium grinding ball particle size is 0.8±0.05 cm, and the large grinding ball particle size is 1.1±0.05 cm. The mass ratio of large, medium and small grinding balls is 1:1.5:1). The mass ratio of various media in the ball mill is selected to be raw material: grinding ball: alcohol equal to 1:1:1.2. The raw material is ball milled for 20 hours at a high energy ball mill of 260 r / min.
[0054] Pre-calcination: After the slurry is stirred and dried at 70°C in a water bath, the raw materials are pre-calcined at 750°C in a muffle furnace.
[0055] Secondary ball milling: grind and crush the raw material block after pre-sintering, weigh it with the doping element Sm according to the stoichiometric ratio, and then put it into the ball mill again at a speed of 260r / min for secondary ball milling. The ball milling parameters are the same as the first ball milling.
[0056] Mixing: PVA and deionized water were stirred in a water bath at 80°C to prepare a 5wt.% PVA solution. The solution was added to the dried secondary ball mill and stirred evenly. Stirring was continued during the granulation process. The water was dried in a water bath at 80°C and the dried powder was sieved through a 60-mesh sieve.
[0057] Suppression: In The mold is filled with ceramic powder with a thickness of about 1 mm, slowly loaded onto the mold at a pressure of 100 MPa and maintained at pressure for 20 seconds.
[0058] Sintering: slowly increase the temperature at a heating rate of 2°C / min, and keep it at 550°C for two hours, then increase the temperature to 1100°C at a heating rate of 2°C / min, keep it at this temperature for 2 hours, and then air-cool it with the furnace.
[0059] Silver coating: After polishing the upper and lower surfaces of the sintered ceramic, apply silver electrodes using a soft brush, dry in an oven at 80°C for 1 hour, and heat treat at 600°C for 10 to 20 minutes.
[0060] Polarization: In a 60℃ silicone oil bath, maintain the voltage at a high voltage DC electric field of 2kV / mm for 25 minutes. After polarization, place it overnight and then test the electrical properties.
[0061] The ceramic produced does not volatilize lead elements during use, meeting the environmental protection requirements of electronic equipment. The ceramic has a high piezoelectric coefficient d 33 =237pC / N, other electrical properties, Kp = 43.72, Qm = 106.54, Tc = 392°C. And the ceramic can maintain good heat aging resistance at around 125°C, and the temperature change rate is only 3%.
[0062] Example 2
[0063] A lead-free KNN-LT piezoelectric ceramic formula, the chemical formula of which is: 0.95 (K 0.55 ,Na 0.45 )NbO 3 -0.05LiTaO 3 -0.6mol.%Sm 2 O 3 .
[0064] The preparation method of the above-mentioned ceramic is as follows:
[0065] Ingredients: First convert the molar ratio into mass ratio according to the chemical structural formula, and then weigh out the required mass of each component such as sodium carbonate, potassium carbonate, lithium carbonate, niobium oxide, tantalum oxide, and samarium oxide.
[0066] Mixing: Put the raw materials potassium carbonate, sodium carbonate, lithium carbonate, niobium oxide and tantalum oxide into the zirconium oxide ball mill, use anhydrous ethanol as solvent, ZrO 2 Grinding balls (grinding ball particle size is selected to be 0.1-1.0cm, among which the small grinding ball particle size is 0.5±0.05cm, the medium grinding ball particle size is 0.8±0.05cm, and the large grinding ball particle size is 1.1±0.05cm. The mass ratio of large, medium and small grinding balls is 1:1.5:1). The mass ratio of various media in the ball mill is selected to be raw material: grinding ball: alcohol equal to 1:1:1.2. The raw material is ball milled for 20 hours at a high energy ball mill of 260r / min.
[0067] Pre-calcination: After the slurry is stirred and dried at 70°C in a water bath, the raw materials are pre-calcined at 750°C in a muffle furnace.
[0068] Secondary ball milling: The pre-sintered raw material block is ground and crushed and mixed with the doping element Sm 2 O 3 After weighing according to the stoichiometric ratio, the mixture was put into the ball mill again and ball milled at a speed of 260 r / min for the second time. The ball milling parameters were the same as those of the first ball milling.
[0069] Mixing: PVA and deionized water were stirred in a water bath at 80°C to prepare a 5wt.% PVA solution. The solution was added to the dried secondary ball mill and stirred evenly. Stirring was continued during the granulation process. The water was dried in a water bath at 80°C and the dried powder was sieved through a 60-mesh sieve.
[0070] Suppression: In The mold is filled with ceramic powder with a thickness of about 1 mm, slowly loaded onto the mold at a pressure of 100 MPa and maintained at pressure for 20 seconds.
[0071] Sintering: slowly increase the temperature at a heating rate of 2°C / min, and keep it at 550°C for two hours, then increase the temperature to 1120°C at a heating rate of 2°C / min, keep it for 2 hours, and then air-cool with the furnace.
[0072] Silver coating: After polishing the upper and lower surfaces of the sintered ceramic, apply silver electrodes using a soft brush, dry in an oven at 80°C for 1 hour, and heat treat at 600°C for 10 to 20 minutes.
[0073] Polarization: In a 60℃ silicone oil bath, maintain the voltage at a high voltage DC electric field of 2kV / mm for 25 minutes. After polarization, place it overnight and then test the electrical properties.
[0074] The ceramic produced does not volatilize lead elements during use, meeting the environmental protection requirements of electronic equipment. The ceramic has a high piezoelectric coefficient d 33 =154pC / N, other electrical properties, Kp=30.15, Qm=101.23, Tc=379°C. The ceramic has a tetragonal phase structure inside. The piezoelectric performance of this formula ceramic is slightly worse than that of the ceramic in Example 1, but it can remain stable from room temperature to about 350°C, with a change rate of only 16%, and has high anti-aging performance.
[0075] Comparative Example 1
[0076] A lead-free KNN-LT piezoelectric ceramic formula, the chemical formula of which is: 0.95 (K 0.55 ,Na 0.45 )NbO 3 -0.05LiTaO 3 -0.2mol.%Sm 2 O 3 The preparation process and parameters of the above ceramics are consistent with those in Example 1.
[0077] Comparative Example 2
[0078] A lead-free KNN-LT piezoelectric ceramic formula, the chemical formula of which is: 0.95 (K 0.55 ,Na 0.45 )NbO3 -0.05LiTaO 3 -0.8mol.%Sm 2 O 3 The preparation process and parameters of the ceramic are basically the same as those in Example 1, except that the sintering temperature is 1120°C.
[0079] Comparative Example 3
[0080] A lead-free KNN-LT piezoelectric ceramic formula, the chemical formula of which is: 0.95 (K 0.55 ,Na 0.45 )NbO 3 -0.05LiTaO 3 -1.0mol.%Sm 2 O 3 The preparation process and parameters of the ceramic are basically the same as those in Example 1, except that the sintering temperature is 1150°C.
[0081] Comparative Example 4
[0082] A lead-free KNN-LT piezoelectric ceramic formula, the chemical formula of which is: 0.95 (K 0.55 ,Na 0.45 )NbO 3 -0.05LiTaO 3 .
[0083] The preparation process and parameters of the ceramic are basically the same as those in Example 1, except that the formula does not contain Sm 2 O 3 .
[0084] Comparative Example 5
[0085] A lead-free KNN-LT piezoelectric ceramic formula, the chemical formula of which is: 0.95 (K 0.55 ,Na 0.45 )NbO 3 -0.05LiTaO 3 -0.4mol.%Sm 2 O 3 The preparation process of the ceramic is basically the same as that of Example 1, except that the sintering temperature is 1200°C.
[0086] Comparative Example 6
[0087] A lead-free KNN-LT piezoelectric ceramic formula, the chemical formula of which is: 0.95 (K 0.55 ,Na 0.45 )NbO 3 -0.05LiTaO 3 -0.4mol.%Sm 2 O3 The preparation process and parameters of the ceramics are basically the same as those in Example 1, except that the ball milling time is only 10 h.
[0088] Comparative Example 7
[0089] A lead-free KNN-LT piezoelectric ceramic formula, the chemical formula of which is: 0.95 (K 0.55 ,Na 0.45 )NbO 3 -0.05LiTaO 3 -0.4mol.%Sm 2 O 3 .
[0090] The preparation method of the above-mentioned ceramic is as follows:
[0091] Ingredients: First convert the molar ratio into mass ratio according to the chemical structural formula, and then weigh out the required mass of each component such as sodium carbonate, potassium carbonate, lithium carbonate, niobium oxide, tantalum oxide, and samarium oxide.
[0092] Mixing: Put the raw materials potassium carbonate, sodium carbonate, lithium carbonate, niobium oxide, tantalum oxide and samarium oxide into a zirconium oxide ball mill, use anhydrous ethanol as solvent, and ZrO 2 Grinding balls (grinding ball particle size is 0.8±0.05cm). The mass ratio of various media in the ball mill is selected as raw material: grinding ball: alcohol equal to 1:1:1.2. The raw material is ball milled for 20 hours at a high energy ball mill of 260r / min.
[0093] Pre-calcination: After the slurry is stirred and dried in a water bath at 70°C, the raw material is pre-calcined in a muffle furnace at 750°C for 5 hours; crushed and then sieved through a 60-mesh sieve;
[0094] The parameters of mixing, pressing, sintering, silvering and polarization are the same as those in Example 1.
[0095] The ceramics produced do not volatilize lead elements during use, and the piezoelectric coefficient of the ceramics is 33 =189pC / N, other electrical properties: Kp=38.72, Qm=98.94, Tc=381℃.
[0096] The experimental results show that the ceramic density of the experimental group (i.e., Examples 1 and 2) and the control group is above 95%, the piezoelectric coefficient is greater than 150 pC / N, and the ceramic has good stability and mechanical properties, which can meet the application requirements of piezoelectric ceramics in electronic devices.
[0097] In summary, the ceramics prepared by the present invention have an electromechanical coupling coefficient greater than 30%, a quality factor greater than 90, and no toxic lead element volatilization occurs during use. In addition, the formula of Example 1 provided by the present invention has the highest piezoelectric coefficient and electromechanical coupling coefficient, but can only remain stable from room temperature to about 125°C. The piezoelectric coefficient of the ceramics in the formula of Example 2 is slightly worse than that of Example 1, but it has ultra-high anti-aging properties and can maintain excellent piezoelectric properties from room temperature to about 350°C, which greatly improves the application temperature of lead-free piezoelectric ceramics and expands the application scenarios of such lead-free piezoelectric ceramics.
[0098] Performance table of the products obtained from the embodiments and comparative examples 1-6
[0099]
Claims
1. A rare earth modified KNN-LT lead-free piezoelectric ceramic, characterized in that: The rare earth modified KNN-LT lead-free piezoelectric ceramic is represented by the following chemical formula: 0.95(K 0.55 , Na 0.45 )NbO3-0.05LiTaO3-xmol.%Sm2O3; in x 0.2~0.6; The rare earth modified KNN-LT lead-free piezoelectric ceramic is prepared by the following process: S1: Potassium source, sodium source, niobium source, lithium source, tantalum source and samarium source are prepared according to the chemical formula of rare earth modified KNN-LT lead-free piezoelectric ceramics, and the other components of the prepared raw materials except the samarium source are put into a ball mill, and organic matter is used as a solvent, and a high-energy ball mill is used for mixing and ball milling at a speed of 250-300 r / min for at least 15 hours, and the fully mixed powder is sieved and put into a corundum crucible and covered, and pre-calcined at 840-860°C for 100-140 minutes to obtain a pre-calcined powder; the potassium source, sodium source, niobium source, lithium source, tantalum source and samarium source are at least one of oxides, carbonates and bicarbonates; S2: Grind and crush the pre-sintered powder and put it into a ball mill again with the prepared samarium source at a speed of 240-280 r / min for a second ball milling for at least 15 h. After ball milling, add 3-8 wt.% of PVA organic binder to granulate to obtain a standby ceramic powder; press the standby ceramic powder into a shape to obtain a ceramic green body; S3: The ceramic green body is placed in a muffle furnace for sintering. The sintering process is divided into two stages. The first stage is 0-550°C, and the heating rate is less than or equal to 4°C / min, so that the PVA organic matter introduced during the granulation process can be fully escaped; the second stage is heated to 1100-1150°C at a heating rate of 4.5-10°C / min and kept warm for at least 100 min; S4: After polishing the upper and lower surfaces of the sintered ceramic sample, the sample was coated with silver electrodes, dried, and then heat treated at 550-650 °C for 10-20 min. S5: The silvered ceramic sample is polarized in silicone oil under the conditions of 60~100 ℃ silicone oil bath and maintained at a high voltage DC electric field of 1~4 kV / mm for 10~30 min.
2. The rare earth modified KNN-LT lead-free piezoelectric ceramic according to claim 1, characterized in that: x It is 0.2~0.
4.
3. The rare earth modified KNN-LT lead-free piezoelectric ceramic according to claim 1, characterized in that: In S1, potassium source, sodium source, niobium source, lithium source, tantalum source and samarium source are prepared according to the chemical formula of rare earth modified KNN-LT lead-free piezoelectric ceramics, and the components except the samarium source in the prepared raw materials are put into a ball mill, and organic matter is used as a solvent, and a high-energy ball mill is used for mixing and ball milling at a speed of 270-290 r / min for 20-25 h. The fully mixed powder is sieved and placed in a corundum crucible and covered for pre-calcination at 840-860°C for 115-125 min. In S2, the pre-sintered powder is ground and crushed, and then put into a ball mill again with the prepared samarium source at a speed of 260 r / min for secondary ball milling for at least 15 hours. After ball milling, 5 wt.% of PVA organic binder is added for granulation to obtain a standby ceramic powder; the standby ceramic powder is pressed into a shape to obtain a ceramic green body; In S3, the ceramic green body is placed in a muffle furnace for sintering. The sintering process is divided into two stages. The first stage is 0-550°C with a heating rate of 1.5-2.5°C / min, so that the PVA organic matter introduced during the granulation process can be fully released. The second stage is heated to 1100-1150°C at a heating rate of 4.5-6°C / min and kept warm for 115-135 min. In S4, the upper and lower surfaces of the sintered ceramic sample are polished, then coated with silver electrodes, dried, and then heat treated at 590-610°C for 10-20 min; In S5, the silvered ceramic sample is polarized in silicone oil under the conditions of 60-100 °C silicone oil bath and maintained at a high voltage DC electric field of 1.8-2 kV / mm for 25 min.
4. The rare earth modified KNN-LT lead-free piezoelectric ceramic according to claim 1, characterized in that: In S1, the molar ratio is first converted into a mass ratio, and then the required mass of each component under a given total mass is weighed; the raw materials potassium carbonate, sodium carbonate, lithium carbonate, niobium oxide, and tantalum oxide are placed in a zirconia ball mill, and anhydrous ethanol is used as a solvent. After mixing and ball milling for 20 hours with a high-energy ball mill at a rotation speed of 270-290 r / min, the fully mixed powder is sieved and placed in a corundum crucible, which is covered and pre-calcined at 840-860 °C for 115-125 min to obtain a pre-calcined powder.
5. The rare earth modified KNN-LT lead-free piezoelectric ceramic according to claim 1, characterized in that: During the ball milling process described in S1, the mass ratio of various media in the ball mill is raw material: grinding ball: alcohol, which is equal to 1:1:1.
2.
6. The rare earth modified KNN-LT lead-free piezoelectric ceramic according to claim 1, characterized in that: In S2, the doping element Sm is added to the ball mill in the form of Sm2O3 particles; the particle size of the Sm2O3 particles is 70-90 microns; In S2, the second ball milling time is 18-25 h.
7. The rare earth modified KNN-LT lead-free piezoelectric ceramic according to claim 1, characterized in that: The average particle size of the standby ceramic powder obtained in S2 is 200-250 microns.
8. The rare earth modified KNN-LT lead-free piezoelectric ceramic according to claim 1, characterized in that: During the sintering process of S3, the powder obtained after the secondary ball milling is buried and sintered in a crucible.
9. The rare earth modified KNN-LT lead-free piezoelectric ceramic according to claim 1, characterized in that: During the sintering process of S3, the heating rate in the first stage was 2 ℃ / min, and the temperature was kept for 2 h to ensure that the adhesive overflowed slowly and fully, thereby reducing the formation of pores inside the ceramic. The heating rate in the second stage was 5 ℃ / min, and the temperature was kept for 2 h to ensure that the ceramic grains grew fully, and finally the furnace was cooled by air cooling.
10. The rare earth modified KNN-LT lead-free piezoelectric ceramic according to claim 1, characterized in that: In S4, after the upper and lower surfaces of the sintered ceramic sample were polished, the silver electrode was coated by a soft brush, dried in an oven at 80 °C for 1 h, and then heat treated at 600 °C for 10-20 min.
Citation Information
Patent Citations
High-stability lead-free piezoelectric ceramic and preparation method thereof
CN113563073A